(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In the pages of "Boburnoma" truth is seen as the main criterion, the true essence of Babur’s life. Babur’s moral point of view, spiritual analysis is extremely ruthless and ruthless. When he evaluates the activities and actions of others based on the requirements, he puts these requirements first on himself, that is, "he first strikes the knife on himself. He went through many good and bad days at the beginning of time, he endured the hardships of life and the joys of life.